(untitled) (E Conference Zone, 2022)
Our times are often referred to as the ‘new world order’ with its ‘new economy’.What this means is that capitalism has been restructured on a global scale, and people of widely different cultural and linguistic backgrounds have been thrown into contact more than ever before. Cultural and linguistic contact may occur in the flows of information and mass media, as well as in the flows of actual people in migration and tourism. Given the ubiquity of cultural and linguistic contact, mergers and hybrids, it is unsurprising that there should be a strong interest in Intercultural Communication, both outside and inside academia. Linguistics as a discipline makes two key contributions to the study of Intercultural Communication. (i) It is the key contribution of discourse analysis and anthropological linguistics to take culture as empirical and cultural identity, difference and similarity as discursive constructions.(ii) Intercultural Communication by its very nature entails the use of different languages and/or language varieties and sociolinguistics, particularly bilingualism studies, illuminates the differential prestige of languages and language varieties and the differential access that speakers enjoy to them